Ruxolitinib, a JAK1/2 Inhibitor, Ameliorates Cytokine Storm in Experimental Models of Hyperinflammation Syndrome - Huarte, Eduardo; Peel, Michael T.; Verbist, Katherine; Fay, Brittany L.; Bassett, Rachel; Albeituni, Sabrin; Nichols, Kim E.; Smith, Paul A. (Frontiers in Pharmacology, 2021)
Hyperinflammatory syndromes comprise a heterogeneous group of disorders characterized by severe inflammation, multiple organ dysfunction, and potentially death. In response to antigenic stimulus (e.g. SARS-CoV-2 infection), overactivated CD8+ T-cells and macrophages produce high levels of proinflammatory cytokines, such as IFN-γ, TNF-α, IL-6, and IL-12. Multiple inflammatory mediators implicated in hyperinflammatory syndromes utilize the Janus kinase–signal transducers and activators of transcription (JAK-STAT) cascade to propagate their biological function. Our findings demonstrate that oral ruxolitinib dosing designed to mimic clinically relevant JAK-STAT pathway inhibition significantly reduces the harmful consequences of immune overactivation in multiple hyperinflammatory models. In contrast to monoclonal antibody therapies targeting a single cytokine, ruxolitinib effectively downregulates the functional effect of multiple cytokines implicated in hyperinflammatory states, without broad immunosuppression.